Cross-Cultural Networks and Exchanges in the Mediterranean Port Cities during the Early Modern Period: The Case of a Jewish Merchant Colony in Marseille - Ferozan, Arazoo (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2024)
This article outlines the commercial engagements of Sephardic networks in Marseille’s Mediterranean trade during the second half of the seventeenth century. More than a century and a half after the expulsion of Jews from this city, the new mercantilist policies of Jean-Baptiste Colbert, minister of finance to Louis XIV, finally enabled Jewish merchants to enjoy trading, settlement, and naturalization privileges. While local policies geared toward foreigners and state-sponsored privileges were often inconsistent, Jewish merchants managed to exploit periods of “limited toleration,” leveraging Marseille’s monopoly in trans-Mediterranean trade to transcend boundaries of faith and economic limitations. In recent decades, scholarship in diaspora and network studies has transformed our understanding of networks beyond the confines of co-religionists, family, and kin by focusing on interfaith and cross-cultural connections. Despite this, the port city of Marseille, its merchant community, and commercial networks have frequently been overlooked in favor of studies centered around France’s Atlantic ports. This case study directs attention to Marseille as a hub of the Sephardi trading diaspora and elucidates how merchants used both formal structures and informal networks, such as communal networks of trade and personal connections, to enhance France’s Mediterranean reach and their influence in an era of global maritime expansion.